2014
DOI: 10.1080/02640414.2014.893369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compliance with different guidelines on physical activity during pregnancy and perceived barriers to leisure physical activity

Abstract: The aims of the this prospective study were to analyze physical activity (PA) engagement during the first and second trimesters, considering the different guidelines published on PA, to document the individual characteristics associated with the accomplishment of these guidelines and to examine pregnant women's perceived barriers to leisure PA, using a socioecological framework. A sample of 133 pregnant women in two stages -at 10-12 weeks' gestation (T1) and 20-22 weeks' gestation (T2) -were evaluated. PA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 50 publications
4
53
2
3
Order By: Relevance
“…mostly advised against strength training [28]. The lack of attention to the subject of exercise combined with both inadequate counselling with regards to mother and child safety and a lack of social support is a barrier to the adoption of the lifestyle intervention "physical exercise" [29]. Our data showed that "well" informed pregnant women tended to have higher activity levels.…”
Section: Discussionmentioning
confidence: 85%
“…mostly advised against strength training [28]. The lack of attention to the subject of exercise combined with both inadequate counselling with regards to mother and child safety and a lack of social support is a barrier to the adoption of the lifestyle intervention "physical exercise" [29]. Our data showed that "well" informed pregnant women tended to have higher activity levels.…”
Section: Discussionmentioning
confidence: 85%
“…The incidence of a sedentary lifestyle during pregnancy ranges from 64.5 to 91.5% and tends to be higher in the third trimester, (4) having a negative impact on live, contributing to the epidemics of obesity and increasing the risk of maternal conditions, such as diabetes mellitus and hypertension. (5,6) …”
Section: Introductionmentioning
confidence: 99%
“…In a British cohort, 48.8% of pregnant women at a GA between 18 and 32 weeks had three or more hours of exercise per week [14], and in an Irish cohort, 21.5% of the pregnant women in the sample were physically active [17]. According to a study performed in Portugal, the main reasons given as a barrier to physical exercise during pregnancy were lack of time, busy schedules, and a dislike for exercise [18].…”
Section: Discussionmentioning
confidence: 99%